2022
DOI: 10.1128/jvi.00546-22
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead O Transcription Factor 4 Restricts HBV Covalently Closed Circular DNA Transcription and HBV Replication through Genetic Downregulation of Hepatocyte Nuclear Factor 4 Alpha and Epigenetic Suppression of Covalently Closed Circular DNA via Interacting with Promyelocytic Leukemia Protein

Abstract: HBV cccDNA is a determining factor for viral persistence and the main obstacle for a cure of chronic hepatitis B. Strategies that target cccDNA directly are therefore of great importance in controlling persistent HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…In our analyses, most of HBV-induced 53BP1 foci colocalized with PML signal. Interestingly, some studies indicated that, in the absence of HBx, PML bodies are important for HBV transcriptional silencing by recruiting inhibitory factors and viral genomes (Niu et al, 2017;Li et al, 2022;Yao et al, 2023a). It would be interesting to perform immune-FISH analyses, able to discriminate between rc and cccDNA, to determine whether PML/53BP1 signals also associate to viral DNA or whether they represent an alternative nuclear anti-viral structure.…”
Section: Discussionmentioning
confidence: 99%
“…In our analyses, most of HBV-induced 53BP1 foci colocalized with PML signal. Interestingly, some studies indicated that, in the absence of HBx, PML bodies are important for HBV transcriptional silencing by recruiting inhibitory factors and viral genomes (Niu et al, 2017;Li et al, 2022;Yao et al, 2023a). It would be interesting to perform immune-FISH analyses, able to discriminate between rc and cccDNA, to determine whether PML/53BP1 signals also associate to viral DNA or whether they represent an alternative nuclear anti-viral structure.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Sp100A, a PML-NB protein, recruits the heterochromatin protein 1 alpha (HP1α) to condense viral DNA, leading to transcriptional repression of the AdV genome [ 22 ]. FOXO4, a PML-NB-associated transcription factor, was found to promote heterochromatinization and silencing of hepatitis B virus (HBV) DNA [ 40 ]. In addition, the structural maintenance of chromosome 5 and 6 (Smc5/6) proteins, which also localize with PML-NBs in human hepatocytes, has been reported to act as RFs for HBV transcription by altering their chromatin organization [ 34 , 41 , 42 ].…”
Section: Virus Epigenetic Restriction Factors (Erfs)mentioning
confidence: 99%
“…Triplex sequence proteins (TRIMs) area family of proteins that play an important role in antiviral innate immunity, and members can effectively inhibit HBV. It has been found that TRIM19 [11] and TRIM38 [12] can inhibit HBV and can be induced by IFN-α. In a study followed for 11.5 years [13], higher rates of HBeAg serologic conversion and negative HBsAg conversion were observed in HBeAg-positive hepatitis B patients treated with interferon, while no significant difference in rates of HBsAg loss was observed between patients treated with short-term and long-term therapy.…”
Section: Interferon Monotherapymentioning
confidence: 99%